Günümüzde seramik takı ve kişisel yorumlarım - Çamaş, Nazan (My University, 2007)
Neredeyse insanlık tarihi ile başlayan takı kullanımı, yaratıları destekleyen akımlar ve takıya yaklaşım biçimleri değişse de, günümüze kadar vazgeçilmezliğini korumuştur. Zaman içinde, teknolojik gelişime paralel olarak takı üretiminde kullanılan malzemeler çeşitlilik göstermiş, takı malzemesi önceleri amaç olarak seçilirken, zamanla tasarımı ön plana çıkaracak araç halini almıştır. Seramiğin takıda kullanılması, değerli süs taşları ve metallerin taklitlerini üretebilme kaygısı ile başlamıştır. Seramik, zamanla başlı başına bir takı malzemesi halini almıştır. Kırılganlığı dezavantaj, sınırsız renk ve dekor seçeneği sağlaması ise avantaj olan seramik, günümüzde birçok sanatçı ve atölye tarafından takıda uygulanmaktadır. Her geçen gün gelişen teknolojisi ile takı sanatında önemini korumaya devam etmektedir.

Using jewelry which is as old as the humanity, has kept on being popular until today, although the trends that support the works of art and the approaches to the jewelry change. The materials that are used for making jewelry has been changing in time due to the technological developments. The materials of jewelry has become the tools to support the designs, although they were just the intents for jewelry in the past. The usage of ceramics in jewelry has begun with the wish of making the fakes of gems and metals. Ceramic has become a jewelry material by itself in time. The fragility of ceramic is a disadvantage, but the unlimited color and décor options are the advantages. Today, many artists and studios are using ceramics for making jewelry. With its every day developing technologies, ceramic keeps on being important in jewelry.
Keywords: Seramik Takı; Takı_Seramik